Tufts administrators and academics, including Tufts President John Cousens, former Harvard University President Charles Eliot, Dean Edith Bush, and Dean Clarence Skinner, photographed with Donald MacJannet when he was awarded an honorary master of arts degree, 1933 - Unknown (Tufts Archival Research Center, 2005)
6x10; (from left to right, beginning third from left) Charles William Eliot, John Albert Cousens, Edith Linwood Bush, Clarence Russell Skinner, (far right) Donald MacJannet